The Effectiveness of Multimedia-Based Biology Learning on the Main Material of the Structure and Function of Tissue-Making Cells in Plants and Animals Class XI IPA at SMA Negeri 1 Onan Ganjang T.P. 2021/2022 - Hudson Sidabutar; Aryanto Lumban Gaol (ARKA INSTITUTE, 2022)
This study aims to determine the effectiveness of multimedia-based biology learning on the structure and function of tissue constituent cells in plants and animals at SMA Negeri 1 Onan Ganjang T.P 2021/2022. The research sample was obtained by random sampling technique. The sample consisted of 2 classes, namely class XI MIA 1 and XI MIA 2. The research design used was a pretest-posttest nonequivalent control group design. The results showed that the posttest average value of the experimental class was 91.26 higher than the control class's posttest average score of 82.6, the average value of the multimedia effectiveness questionnaire in the experimental class was 95.7 higher than the control class's average value. 60.7, and the average value of the teacher's questionnaire regarding the effectiveness of multimedia as a teaching material is 90. The effectiveness value obtained by comparing the n-gain of the experimental class and the control class is 1.65 which shows that multimedia is more effective than student worksheets. So it can be concluded that multimedia as a teaching material is effectively used in the structure and function of cells making up plant and animal tissues in class XI MIA at SMA Negeri 1 Onan Ganjang T.P 2021/2022.